HUBUNGAN PENGETAHUAN SIKAP DAN PRAKTIK PERAWAT TERHADAP UPAYA PENCEGAHAN PASEN JATUH - Wulandari, Ranti; Sianturi, Sondang Ratnauli (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
The incidence of falling patients has a detrimental effect on the patient, namely the impact of physical injury. Fall prevention is one indicator in patient safety. Knowledge, attitudes and practices of nurses with the ability of nurses play an important role in the implementation of patient safety, especially in the prevention of falling patients. This study aims to determine the relationship of knowledge, attitudes and practices of nurses to efforts to prevent patients falling. This research is a quantitative descriptive correlation study. The respondents were nurses who worked in adult inpatients at Jakarta X Hospital as many as 91 nurses using the accidental sampling method. The results of univariate research data obtained 46.1% of respondents aged 26-35 years, 70% were educated nursing Diploma, 35.1% have worked <5 years in the hospital , 41.8% have competent level, 61.5% have good knowledge, 54.9% have good attitude, 51.6% have good practice and 69.2% have good prevention of falling patients. The results of the bivariate study showed a significant relationship between knowledge (p value 0.016), attitude (p value 0.013), practice (p value 0.011) with efforts to prevent patients falling. Respondent have used the Morse scale and made efforts to prevent patients from falling in the hospital. The results of this study are expected to be used to improve the quality of patient care prevention services related to patient safety (patient safety), especially in inpatient rooms.Keywords: Nurses knowledge; patient safety; prevention of falling pat